Amicus Curiae Sebagai Alat Bukti Dalam Proses Pembuktian Sistem Peradilan Pidana Indonesia - Anwar, Cecareno Gilbrani; Simangunsong, Frans (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Amicus curiae is a third party that provides information, opinions, or legal analysis to the court to assist in decision-making. In the Indonesian criminal justice system, the existence of amicus curiae is still limited, but its potential is significant as additional evidence, especially in complex cases involving the public interest. This study aims to analyze the role of amicus curiae in providing factual and legal information, its relevance as evidence, and the challenges of its implementation in Indonesia. The normative legal research method uses a Statutory approach and a Conceptual Approach. The results of the study indicate that although not explicitly regulated in the Criminal Procedure Code, the practice of amicus curiae can strengthen the criminal justice process by providing an independent third-party perspective, especially in cases of human rights violations, corruption, and transnational crimes. The existence of Amicus Curiae is only limited to being a guideline in the Indonesian Criminal Justice System. However, in reality, Amicus Curiae does not yet have binding legal force as a process of evidence in the Indonesian criminal justice system. Therefore, in the future, Indonesia will regulate in Laws and Regulations regarding the existence of amicus curiae in the Indonesian Criminal Justice System.